The Pioneers of Development Economics: Great Economists on Development - De Dios, Emmanuel S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
The recent period in the growth of economics has witnessed a surprising revival of interest in the problems of development. Many of the profession’s “big names”—Stiglitz, Sachs, Barro, Krugman, Helpman, and North, to mention only a few—have lent their names to the rediscovery of a field whose independent existence was denied not too long ago in many teaching departments. With this recently gained respectability, the current professional mainstream seems almost to be saying, “We are all development economists now.”